2012
DOI: 10.1007/s11274-012-1184-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance of two isolates of Isaria fumosorosea from hot climate zones in solid and submerged cultures and thermotolerance of their propagules

Abstract: Isaria fumosorosea frequently causes mycosis of agricultural pests in the hot semiarid and dry tropical regions of Mexico. Because temperature tolerance restricts the use of fungal biopesticides, we investigated two isolates from these areas for possible development into mycoinsecticides for use in hot weather agricultural zones. We studied the effects of culture system (solid or submerged cultures) and temperature on the fungal growth, extracellular enzyme production, pathogenicity, and thermotolerance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Thus, one of the problems in employing massively produced commercial EPFs can be their variation in pathogenicity when used in different climatic conditions [87]. Further, Esther et al [88] showed that different Isaria fumosorosea EPF strains express different thermal tolerance towards the growth rate according to the temperature range of their geographical origins. Therefore, specific selection and commercialization of different EPF isolates adapted to different climatic conditions and soil properties can compensate for the EPFs’ potential lack of efficiency as root pest bio-control.…”
Section: Fungimentioning
confidence: 99%
“…Thus, one of the problems in employing massively produced commercial EPFs can be their variation in pathogenicity when used in different climatic conditions [87]. Further, Esther et al [88] showed that different Isaria fumosorosea EPF strains express different thermal tolerance towards the growth rate according to the temperature range of their geographical origins. Therefore, specific selection and commercialization of different EPF isolates adapted to different climatic conditions and soil properties can compensate for the EPFs’ potential lack of efficiency as root pest bio-control.…”
Section: Fungimentioning
confidence: 99%
“…Thus, the optimization performed in the culture medium based on Esther et al (2013) was satisfactory and can be adopted for submerged conidia production of C. javanica.…”
Section: Bioassay With Methomyl-resistant and Non-resistant Dalbulus ...mentioning
confidence: 96%
“…There was a significant difference among the tested modified culture media (P < 0.05) (Figure 10). The M4, Esther et al (2013) modified with NS1 as the nitrogen source yielded a significantly higher final production of 2.61 × 10 8 submerged conidia mL -1 .…”
Section: Cordyceps Javanica (Esalq 1296) Submerged Conidia Productionmentioning
confidence: 96%
See 2 more Smart Citations